TEATRO : HA LLEGADO UN INSPECTOR ; TRES PIEZAS SOBRE EL TIEMPO - Priestley, J.B ((Gran Teatro del Mundo), 1964)
TRADUCCION DE: AN INSPECTOR CALLS THREE-TIME PLAYS: DANGEROUS CORNER. TIME AND THE CONWAYS. I HAVE BEEN HERE BEFORE